One‐Step Microwave Approach to Generate Carbon Dots/Gelatin Composite with Both Thermoresponsive Sol–Gel Transition and Fluorescence Properties. Issue 5 (30th March 2020) - Wang, Xia; Liu, Hui; Wu, Wencheng; Xiong, Yanfei; Chen, Wei; Cao, Kaiyuan; Wang, Yifeng; Chen, Yanjun
Abstract: Carbon dots (CDs) have drawn considerable research interest for their attractive applications in sensors, bioimaging, and photonic devices. Here, an aqueous gelatin solution is employed as the only reactant to directly generate a CDs/gelatin composite through a green and simple one‐step microwave approach. The resulting CDs/gelatin composite owns a typical excitation‐dependent photoluminescence property that comes from CDs, which can be potentially applied for multicolor fluorescence bioimaging. More importantly, the CDs/gelatin composite possesses a thermoresponsive sol–gel transition property that is associated with gelatin, which can be exquisitely enlisted to fabricate CDs/gelatin gel beads and fluorescent gel patterns. Also the release of CDs from the gel beads can be triggered by the thermoresponsive sol–gel transition. Thus, for the first time this study creates the CDs/gelatin composite with both thermoresponsive sol–gel transition and fluorescence properties, which is promising for applications in stimuli‐responsive materials, nanocomposites, controlled release, and fluorescence imaging. Abstract : This study presents a simple and environmentally friendly one‐step microwave approach to prepare a carbon dots (CDs)/gelatin composite using an aqueous gelatin solution as the only reactant. The resulting CDs/gelatin composite not only has an excitation‐dependent fluorescence property that comes from CDs, but also possesses a thermoresponsive sol–gel transition property that is associated with gelatin.